Відображення зв’язку людини й природи в художньому дискурсі - Козак, Софія Веніамінівна; Kozak, Sofia V. (Херсонський державний університет, 2017)
In the article the analysis of the frame structures, which depict the relationship between man and nature in the works of fiction, have been analyzed. The research have been carried out on the material of the English belles-lettres discourse represented by the novels of the English writer Thomas Hardy “The Woodlanders”, “Tess of the D’Urbervilles” and “The Return of the Native”. The terminal elements, that represent frames NATURE and MAN and describe people’s inner world on the basis of the comparison with the natural phenomena, have been analyzed. У статті здійснено аналіз фреймових структур, які зображують взаємозв'язок людини й природи у творах художньої літератури. Дослідження проведене на матеріалі англомовного літературно-художнього дискурсу, представленого романами англійського письменника Томаса Гарді «У краю лісів», «Тесе із роду д'Ербервіллів» і «Повернення на батьківщину». Проаналізовано термінальні елементи, що втілюють фрейми ПРИРОДА й ЛЮДИНА й описують внутрішній стан людини на основі порівняння з природними явищами.
The representation of the relationship between man and nature in fiction discourse
Keywords: frame; frame structure; terminal element; man; nature; relation; фрейм; фреймова структура; термінальний елемент; людина; природа; зв'язок